2015
DOI: 10.1590/s0100-720320150005419
|View full text |Cite
|
Sign up to set email alerts
|

Fatores nutricionais e psicológicos associados com a ocorrência de picamalácia em gestantes

Abstract: sonAly Petronilho heidelmAnn 3 CláudiA sAunders 4 Resumo OBJETIVO: Avaliar fatores nutricionais e psicológicos associados com a ocorrência da prática da picamalácia em gestantes atendidas em maternidade pública do Rio de Janeiro, Brasil. MÉTODOS: Estudo descritivo, de caráter exploratório, realizado com 13 gestantes (idades entre 16 e 40 anos) com diagnóstico de picamalácia na gestação atual identificada em entrevista padronizada na consulta com nutricionista que abordava questões sobre ocorrência e frequência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 23 publications
3
12
0
16
Order By: Relevance
“…As previous study suggested (Ayeta et al, 2015), it was observed a prevalence of two types of coping among pregnants with pica: "coping based on the searching for social support" and "coping based on the religious practice or imaginative thoughts". Regarding to the "coping based on the searching for social support" we observed that family support was very important for most of those women, either because they share the same food preferences, or because family members prevent the fulfi llment of uncontrolled desire for substances, sometimes toxic (detergents, for example) or exotic (mango with salt, lemon with salt, etc.).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…As previous study suggested (Ayeta et al, 2015), it was observed a prevalence of two types of coping among pregnants with pica: "coping based on the searching for social support" and "coping based on the religious practice or imaginative thoughts". Regarding to the "coping based on the searching for social support" we observed that family support was very important for most of those women, either because they share the same food preferences, or because family members prevent the fulfi llment of uncontrolled desire for substances, sometimes toxic (detergents, for example) or exotic (mango with salt, lemon with salt, etc.).…”
Section: Discussionmentioning
confidence: 80%
“…Pregnant women who practice pica show signifi cant signs of stress at some level (Ayeta et al, 2015;Woods, Melville, Guo, Fan, & Gavin, 2010), and many of them develop signs of anxiety during pregnancy (Vythilingum, 2008). Psychological variables, such as anxiety and depression, can affect the mother during prenatal period, contributing to negative obstetric outcomes, such as prematurity, low birth weight and child development problems (Ding et al, 2014;Van Batenburg-Eddes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations